DIGITAL ENTREPRENEURSHIP - Setyawan, Danny Surya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Many studies have proven entrepreneurship as a key factor for economic growth and also reducing unemployment. To become a successful entrepreneur, it is very important to understand all the concepts related to entrepreneurship. Method: This study employs a qualitative approach to explore digital entrepreneurship, focusing on its characteristics, opportunities, and challenges. A literature review was conducted to analyze existing research on digital business models, ICT-based entrepreneurship, and market trends. Secondary data sources, including scholarly articles and industry reports, were utilized to understand the evolution of digital entrepreneurship and its impact on employment and business growth. Results: To face the market competition and achieve business goals, every entrepreneur must keep up with the changes that occur in the tastes and preferences of customers and also in the market. Sometimes it is necessary to use some digital technologies and modern software to communicate with customers and also to increase the value of the product. Since today's world is largely dependent on national and multinational technology, it is important to incorporate these technologies into the business. Novelty: Digital entrepreneurship plays a vital role in empowering entrepreneurs to perform all the activities accurately and effectively. Since it is the process of using digital applications, it helps every entrepreneur to increase the market value of their products and grow the business both traditionally and technologically. Since information and communication technology (ICT) capabilities are an essential element for the success of digital companies, it is important to know how these technologies help people to improve their businesses. This can enable every individual involved in business to gain knowledge about digital entrepreneurship.